Usage-centered, efficient, and sustainable: an IoT-driven transformation of water heaters - Hassan Habib Chaudhry; Ramish Majeed Raja; Muhammad Azmeer Zahid; Nauman Zaffar; Muhammad Hamad Alizai; Naveed Anwar Bhatti (Data-Centric Engineering, 2024)
In developing countries, a significant amount of natural gas is used for household water heating, accounting for roughly 50% of total usage. Legacy systems, typified by large water heaters, operate inefficiently by continuously maintaining a large volume of water at a constant temperature, irrespective of demand. With dwindling domestic gas reserves and rising demand, this increases dependence on expensive energy imports.